Evaluation of antibacterial activity and molecular characterization of bacteria from Holothuria atra intestine collected from anthropogenic and non-anthropogenic region in Karimunjawa, Indonesia - Bambang Sulardiono; NINIEK WIDYORINI; DJOKO SUPRAPTO; DIAH AYUNINGRUM; ARIF RAHMAN (Society for Indonesian Biodiversity, 2020)
Abstract. Sulardiono B, Widyorini N, Suprapto D, Ayuningrum D, Rahman A. 2020. Evaluation of antibacterial activity and molecular characterization of bacteria from Holothuria atra intestine collected from anthropogenic and non-anthropogenic region in Karimunjawa, Indonesia. Biodiversitas 21: 3149-3155. Evaluation of antibacterial activity and molecular characterization of bacteria from the intestine of Holothuria atra is needed in the anthropogenic region of Menjangan Besar, Karimunjawa. The research aims to evaluate antibacterial activity and molecular characterization of bacteria from intestine of Holothuria atra collected from anthropogenic and non-anthropogenic regions in Karimunjawa, Indonesia. Sea cucumber samples were collected at Menjangan Besar waters as anthropogenic region (code of HM) and Alang-alang waters as non-anthropogenics region (code of HA), Karimunjawa National Park, Indonesia. The H. atra sample collection was using purposive sampling method. Examination of the bacteria from isolation until molecular characterisation was done at the Tropical Marine Biotechnology Laboratory, Uiversitas Diponegoro. The isolation process was conducted using spread plate method, followed by bacterial isolates purification using streak plate method. Screening of antibacterial activity using the agar plug method, as well as molecular identification was conducted by 16S rDNA PCR amplification. The results of this study indicated that a total of 26 bacterial strains were successfully isolated from sea cucumber intestine, consisted of eleven bacterial isolates from H. atra in Menjangan Besar waters and the rest fifteen isolates from H. atra in Alang-alang waters. The preliminary assay of antibacterial test showed H. atra in both waters have potential bacterial isolates. Those bacterial isolates with antibacterial activity were HM1.2 and HA1.1, which based on molecular identification, showed isolates HM1.2 and HA1.1 had the closest similarity with Bacillus paramcoides and Vibrio alginolyticus consecutively, with BLAST homology 98% and 99%. The accession number for both isolates were LC550090 and LC550089, respectively.